Enhancing the construction site safety knowledge and awareness amongst civil engineering undergraduate students / Herda Balqis Ismail ... [et al.] - Ismail, Herda Balqis; Yusuf, Ahmad Idzwan; Lee, Siong Wee; Mohamed Yusof, Mohamed Khatif Tawaf; Abu Talip, Adrina Rosseira; Mat Salleh, Mohd Zulkhairi; Sarbini, Noor Nabilah (Universiti Teknologi MARA, 2023)
There are numerous hazards that could harm the workers and cause accidents in the construction industry. Therefore, undergraduate students need to be exposed to and educated about the construction site safety. A study in exploring the knowledge and awareness of construction site safety among students of civil engineering is significant as this group of students are the prospective industry’s personnel in the future. This study is conducted to: (1) determine students’ knowledge of construction site safety management, (2) investigate the level of students’ awareness toward site safety practices; and (3) indicate students’ understanding of construction site accident implication. Respondents are required to answer a questionnaire survey non-verbally to indicate their knowledge and awareness of the construction site safety. Statistical analysis is used to analyse the collected data. From the findings, there are no differences on the level of knowledge and awareness between female and male students towards the site safety aspects. Both groups of students have a high level of knowledge on the site safety management and site accident implication. Students are also aware of the elements of safety practices implemented at the construction site. However, a few aspects need to be enhanced in the learning and teaching process. Indirectly, the findings provide supplementary information to examine the construction safety education which needs to be embedded in the programme curriculum and system. It will be beneficial in improving the humanity aspects among students as these students will be exposed to the most hazardous workplace in the future.